2021
DOI: 10.1111/ggi.14140
|View full text |Cite
|
Sign up to set email alerts
|

Perceived declining physical and cognitive fitness during the COVID‐19 state of emergency among community‐dwelling Japanese old‐old adults

Abstract: Aim Perceived health status, including physical and cognitive fitness, will be negatively associated with future health conditions among old‐old adults. The coronavirus disease 2019 (COVID‐19) pandemic has caused sudden changes in lifestyle. Thus, this study examined the associations of participation in an exercise class before the COVID‐19 pandemic and the exercise habits and disruption to the rhythms of daily life during the COVID‐19 state of emergency with perceived declining physical and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
2
30
2
4
Order By: Relevance
“…Our results demonstrated that during program interruption, participant physical and psychoaffective status severely worsened and frailty increased. These findings are congruent with those of Makizako et al (2021) , where a higher perception of declining physical and cognitive fitness during the state of emergency was observed in older adults who had participated in an exercise class before the COVID-19 pandemic. These changes could be caused by legal restrictions, fear of going out related to the COVID-19 pandemic, and/or program interruption.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results demonstrated that during program interruption, participant physical and psychoaffective status severely worsened and frailty increased. These findings are congruent with those of Makizako et al (2021) , where a higher perception of declining physical and cognitive fitness during the state of emergency was observed in older adults who had participated in an exercise class before the COVID-19 pandemic. These changes could be caused by legal restrictions, fear of going out related to the COVID-19 pandemic, and/or program interruption.…”
Section: Discussionsupporting
confidence: 88%
“…Among the few reports on physical fitness in older adults during the COVID-19 pandemic, one was based on studies showing the effects of exercise cessation in other circumstances ( Kirwan et al, 2020 ). However, Makizako et al (2021) showed that 43% of older adults under study perceived declining physical fitness during the COVID-19 pandemic; this study used a wide sample of participants of similar ages to the participants in our study.…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that vigorous and moderate intensity PA were significantly lower during and post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown [ 16 ]. More than 40% of community-dwelling Japanese old-old adults perceived a decline their physical fitness during the COVID-19 state of emergency [ 17 ]. Although several studies have reported decreased PA due to the COVID-19 epidemic [ 18 ], few have determined its impact on perceived health and PA recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Responders who reported a history of stroke, Parkinson disease, dementia, depression, and/or other neurological disorders known to influence reduced PA and cognitive impairment were excluded. [ 23 , 24 ] In addition, based on a previous study, [ 24 ] responders who reported more than 960 min/day or 0 min/day of total PA time and more than a tenfold change (increasing or decreasing) in total PA were also excluded. Finally, data from 1967 middle-aged and older Japanese adults were analyzed.…”
Section: Methodsmentioning
confidence: 99%